Adapting the Theory of Planned Behavior to Analyze Smoking Intentions Among Adolescents in Urban School - Nabila Luthfia Nurseha; Elia Nur A’yunin (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2024)
Introduction: The prevalence of smoking among adolescents continues to increase each year. The Theory of Planned Behavior states that behavior is preceded by intention. Objective: This study aims to identify the factors associated with and most dominant in influencing smoking intentions among adolescents. Method: This research is quantitative with a cross-sectional study design. The study was conducted at State Junior High School 3 in South Tangerang City, which is located in an urban area. The research sample consisted of 276 adolescents who were non-active smokers, selected using a proportional stratified sampling technique, and data collection was carried out through a questionnaire. Data analysis included univariate analysis, bivariate analysis using the chi-square test, and multivariate analysis using multiple logistic regression. Result: The results showed that most adolescents had strong smoking intentions (56.5%), supportive attitudes toward smoking (52.2%), negative subjective norms (54.7%), and weak perceived control over smoking behavior (55.8%). There was a significant relationship between smoking attitudes (PR=2.658; 95% CI=2.028-3.485; P<0.05), subjective norms (PR=3.338; 95% CI=2.439-4.568; P<0.05), and perceived control over smoking behavior (PR=2.739; 95% CI=2.046-3.666; P<0.05) with smoking intention. Subjective norms were identified as the dominant variable influencing the intention. Conclusion: There is a relationship between attitude, subjective norm, and perceived behavioral control with respect to smoking intention, with subjective norm being the dominant variable influencing intention. Therefore, it is essential to intensify peer education programs to influence peers to avoid smoking, as well as to conduct a deeper analysis of the factors shaping subjective norms and design school-based interventions specifically targeting changes in these norms.